Induced Pluripotent Stem Cells-Derived Mesenchymal Stem Cells Attenuate Cigarette Smoke-Induced Cardiac Remodeling and Dysfunction - Liang, Yingmin; Li, Xiang; Zhang, Yuelin; Yeung, Sze Chun; Zhen, Zhe; Ip, Mary S. M.; Tse, Hung Fat; Lian, Qizhou; Mak, Judith C. W. (Frontiers in Pharmacology, 2017)
The strong relationship between cigarette smoking and cardiovascular disease (CVD) has been well-documented, but the mechanisms by which smoking increases CVD risk appear to be multifactorial and incompletely understood. Mesenchymal stem cells (MSCs) are regarded as an important candidate for cell-based therapy in CVD. We hypothesized that MSCs derived from induced pluripotent stem cell (iPSC-MSCs) or bone marrow (BM-MSCs) might alleviate cigarette smoke (CS)-induced cardiac injury. This study aimed to investigate the effects of BM-MSCs or iPSC-MSCs on CS-induced changes in serum and cardiac lipid profiles, oxidative stress and inflammation as well as cardiac function in a rat model of passive smoking. Male Sprague-Dawley rats were randomly selected for exposure to either sham air (SA) as control or 4% CS for 1h per day for 56 days. On day 29 and 43, human adult BM-MSCs, iPSC-MSCs or PBS were administered intravenously to CS-exposed rats. Results from echocardiography, serum and cardiac lipid profiles, cardiac antioxidant capacity, cardiac pro- and anti-inflammatory cytokines and cardiac morphological changes were evaluated at the end of treatment. iPSC-MSC-treated group showed a greater effect in the improvement of CS-induced cardiac dysfunction over BM-MSCs-treated group as shown by increased percentage left ventricular ejection fraction and percentage fractional shortening, in line with the greater reversal of cardiac lipid abnormality. In addition, iPSC-MSCs administration attenuated CS-induced elevation of cardiac pro-inflammatory cytokines as well as restoration of anti-inflammatory cytokines and anti-oxidative markers, leading to ameliorate cardiac morphological abnormalities. These data suggest that iPSC-MSCs on one hand may restore CS-induced cardiac lipid abnormality and on the other hand may attenuate cardiac oxidative stress and inflammation via inhibition of CS-induced NF-κB activation, leading to improvement of cardiac remodeling and dysfunction. Thus, iPSC-MSCs may be a promising candidate in cell-based therapy to prevent cardiac complications in smokers.